2021
DOI: 10.1177/2333794x211016789
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of HemotypeSC as a Point-of-Care Testing Device for Sickle Cell Disease: Findings from a Southwestern State in Nigeria and Implications for Patient Care in Resource-Poor Settings of sub-Saharan Africa

Abstract: This study aimed to determine the performance of a rapid, point-of-care testing device (HemotypeSC)™ for diagnosing sickle cell disease (SCD) relative to 2 commonly-used methods compared to DNA polymerase chain reaction (PCR) as the reference standard. The diagnostic performance of (HemotypeSC)™ in diagnosing SCD and determining various other Hb genotypes relative to high performance liquid chromatography (HPLC) and cellulose acetate Hb electrophoresis in alkaline buffer (CAE) was investigated among 156 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Our findings agree with previous studies suggesting a specificity and specificity of 100% (Nnodu et al, 2019) (Olatunya et al, 2021 for HbS and HbC in ideal conditions using the standard HemoTypeSC POCT procedure. Nnodu et al, worked on 1,121 samples and compared HemoTypeSC POCT with HPLC (GOLD Standard).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings agree with previous studies suggesting a specificity and specificity of 100% (Nnodu et al, 2019) (Olatunya et al, 2021 for HbS and HbC in ideal conditions using the standard HemoTypeSC POCT procedure. Nnodu et al, worked on 1,121 samples and compared HemoTypeSC POCT with HPLC (GOLD Standard).…”
Section: Resultssupporting
confidence: 93%
“…They got a sensitivity of; 0.989 (AA), 0.983 (AS), 1.000 (SS), 0.933 (AC), and Specificity of: 0.993 (AA), 0.992 (AS), 0.999 (SS), 1.000 (AC). Olatunya et al (2021) in 2021 compared Cellulose Acetate Electrophoresis, HemoTypeSC POCT and HPLC methods with PCR in 158 participants. HemoTypeSC showed both a Sensitivity and Specificity of 1.00 (100%) for AA, AC, AS, SC, and SS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated the diagnostic accuracy of two POC tests sickle SCAN® and hemotypeSC™ and both test methods displayed high sensitivity and specificity as compared to reference methods. HemotypeSC™ displayed the sensitivity and specificity of 100% in identifying all Hb phenotypes, all study participants were correctly identified and this is in agreement with previous studies done in SSA to assess the feasibility of the test in limited‐resource countries 18–20 . On the other hand, sickle SCAN® showed sensitivity and specificity of 99.5% and 100%, respectively, in identified all Hb phenotypes.…”
Section: Discussionsupporting
confidence: 89%
“…HemotypeSC™ displayed the sensitivity and specificity of 100% in identifying all Hb phenotypes, all study participants were correctly identified and this is in agreement with previous studies done in SSA to assess the feasibility of the test in limited-resource countries. [18][19][20] On the other hand, sickle SCAN ® showed sensitivity and specificity of 99.5% and 100%, respectively, in identified all Hb phenotypes. Sickle SCAN ® was able to identify Hb AA and Hb SS perfectly, but as compared to hemotypeSC™ the sensitivity for sickle SCAN ® in identifying Hb AS declined to 97.0%, the decline of sickle SCAN in detecting Hb AS has also been reported in the previous study.…”
Section: Discussionmentioning
confidence: 97%
“…All study participants with malaria were screened for sickle cell hemoglobin. Sickle cell haplotypes were identified as recently published [ 28 ].…”
Section: Methodsmentioning
confidence: 99%